A Systematic Review of the Soft-Tissue Connections Between Neck Muscles and Dura Mater: The Myodural Bridge. Issue 1 (1st January 2017) - Palomeque-del-Cerro, Luis; Arráez-Aybar, Luis A.; Rodríguez-Blanco, Cleofás; Guzmán-García, Rafael; Menendez-Aparicio, Mar; Oliva-Pascual-Vaca, Ángel
Abstract : Study Design: Systematic review. Objective: To elucidate the existence of soft tissue connections between the neck muscles and cervical dura mater. Summary of Background Data: Several studies discuss the existence of a cervical myodural bridge; however, conflicting data have been reported. Methods: Searches were conducted in the PubMed, Web of Science, Cochrane Library, and PEDro databases. Studies reporting original data regarding the continuity of non–post-surgical soft tissue between the cervical muscles and dura mater were reviewed. Two reviewers independently selected articles, and a third one resolved disagreements. Another two researchers extracted the methodology of the study, the anatomical findings, and evaluated the quality of the studies using Quality Appraisal for Cadaveric Studies Scale. A different third researcher resolved disagreements. Results: Twenty-six studies were included. A soft tissue connection between the rectus capitis posterior minor, the rectus capitis posterior major, and the obliquus capitis inferior muscles seems to be proved with a strong level of evidence for each one of them. Controversy exists about the possible communication between the dura mater and the upper trapezius, rhomboideus minor, serratus posterior superior, and splenius capitis by means of the ligamentum nuchae. Finally, there is limited evidence about the existence of a soft tissue connection between rectus capitis anterior muscle and the dura mater. Conclusion: There is a continuity of soft tissue between the cervical musculature and the cervical dura mater; this might have physiological, pathophysiological, and therapeutic implications, and going some way to explaining the effect of some therapies in craniocervical disorders. Level of Evidence: N/A